Pengaruh Spiriziomacare terhadap Tingkat Kecemasan dan Tanda Vital Pasien Pre-Kateterisasi Jantung - Sari, Yulia Indah Permata; Oktarina, Yosi; Sari, Putri Irwanti; Nurhusna, Nurhusna (Jurnal Akademika Baiturrahim Jambi, 2025)
Cardiac catheterization is an invasive procedure for coronary heart disease that can trigger anxiety. This anxiety activates the HPA axis and the sympathetic nervous system, which increases heart rate and blood pressure, worsening cardiovascular conditions and raising the risk of complications such as bleeding and vascular occlusion. Therefore, patient anxiety before catheterization must be addressed to prevent complications. Spiriziomacare is a spiritual intervention that combines dhikr (remembrance of God) and aromatherapy to reduce anxiety. This study aims to assess the effect of Spiriziomacare on anxiety and vital signs in pre-cardiac catheterization patients. Using a pre-experimental design with a one-group pre and post-test design, a purposive sampling technique was applied to 40 patients at RSUD Raden Mattaher Jambi. Data collected included demographic information, anxiety scores, systolic and diastolic blood pressure, heart rate, and respiratory rate. The results show a significant reduction in systolic blood pressure (from 132.63 to 129.63 mmHg), diastolic blood pressure (from 83.10 to 83.15 mmHg), heart rate (from 80.13 bpm to 77.93 bpm), and respiratory rate (from 22.4 to 21.65 breaths per minute) after the intervention. Bivariate analysis revealed a significant effect of Spiriziomacare on anxiety (p=0.000), systolic blood pressure (p=0.015), diastolic blood pressure (p=0.017), heart rate (p=0.045), and respiratory rate (p=0.000). Spiriziomacare effectively reduces anxiety and stabilizes the vital signs of patients before cardiac catheterization.